Identification and 3D modeling of bioactive peptides from Lactobacillus brevis RAMULAB49 protein hydrolysate with in silico ERK1 phosphorylation inhibition activity targeting diabetic nephropathy - Reshma Mary Martiz; Ramith Ramu; Hemalatha Nambisan; Ameer Suhail; Mohammad Raish; Shashank M. Patil; Ashwini P.; Mahesh B.; Maciej Przybyłek; Piotr Bełdowski; Alina Sionkowska; Kefeng Li; et al. (PLoS ONE, 2025)
Diabetic nephropathy (DN) poses a significant health challenge, necessitating novel therapeutic approaches. In this study, we isolated proteins from cell-free supernatant (CFS) from the culture of the lactic acid bacteria Lactobacillus brevis RAMULAB49 strain. The proteins were subjected to simulated in vitro gastrointestinal digestion using gut enzymes – pepsin, pancreatin, and trypsin. The hydrolysates were filtered using 3kDa threshold ultra-centrifugal filters and were desalted using C18 disks. This was followed by nLC-ESI MS/MS tandem mass spectrometry-based identification of peptides, leading in the identification of a of 258 unique peptides across three enzyme combinations. The resultant sequences were made into peptide library construction based on their, bioactivity scores, allergenicity, toxicity, and antidiabetic potential, a total of 10 peptides was constructed and modeled in 3D. On the other hand, 266 DN associated genes were identified using a network pharmacology approach. The resultant protein-protein (PPI) network was analysed using the gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment approaches, resulting in identification of critical pathways, ERK1, PI3K-Akt, EGRF and TNF signaling as significantly involved in DN, where, ERK1 emerging as a key node due to its involvement in cell proliferation, inflammation, and fibrosis associated with DN. Top two 3D-modelled bioactive peptides were selected for interaction study with the target protein ERK1. Peptide TNEDPYTIDVES showed a strong binding energy of −9.9 kcal/mol, at the ATP-binding site and dynamics simulations confirmed the structural stability of this complex over 100 ns, showing consistent hydrogen bond interactions and RMSD values below 2.5 Å. These findings suggest that TNEDPYTIDVES may act as a competitive ERK1 inhibitor by occupying the adenine-mimicking ATP-binding cleft, thereby interfering with phosphorylation activity. This integrative approach highlights L. brevis RAMULAB49 strain derived peptides as promising candidates for the development of peptide-based therapeutics target and could pave the way for new drug development treating diabetic nephropathy.